Focus on Epithelialized Palatal Grafts. Part 1: Multiple Adjacent Recession Defects in the Mandibular Anterior. Issue 4 (28th September 2018) - Berridge, Joshua P.; Johnson, Thomas M.; Lane, Jonathan D.; Miller, Preston D.
Abstract : Introduction: The mandibular anterior can be a challenging anatomic location for achieving root coverage irrespective of the selected graft and surgical technique. The epithelialized palatal graft (EPG), often dismissed in deference to esthetic and patient‐centered considerations, is well‐suited for treating gingival recession in this region. Although a considerable volume of data exists assessing root coverage procedure outcomes, little evidence supports superiority of any one technique specifically applied to the mandibular anterior. Case Presentation: Two periodontally and systemically healthy patients with multiple adjacent Class I and III recession defects in the mandibular anterior were treated with EPG. Recipient site dimensions in one case obligated bilateral palatal donor sites. In this case, the two autogenous grafts were carefully sutured extraorally before placement. Favorable increases in attached gingival dimensions and partial or complete root coverage were noted after 12‐ or 18‐month follow‐up periods. In the case requiring bilateral donor sites, no transition between the two grafts could be appreciated after healing. Conclusions: Overall, subepithelial connective tissue graft (SCTG)‐based techniques reportedly produce higher mean root coverage percentages and more frequent complete root coverage compared with EPG. However, when observations are limited to the mandibular anterior, there are insufficient data to conclude SCTG is superior to EPG. In the presented cases, EPG at multiple adjacent mandibular anterior recession defects produced favorable clinical outcomes. Extraoral suturing of bilaterally harvested grafts facilitated graft stabilization and minimized irregularities in gingival architecture after healing.